Valsartan induced exanthematous macular skin lesions - Che' Man, Mohamad; Che Alhadi, Shahidah; Azmi, Nurul Husna; Mohd Arifin, Siti Roshaidai; Amiruddin, Salman (2020)
Valsartan is one of the common angiotensin II receptor blocker (ARB) that typically used in the treatment of hypertension, heart failure and chronic kidney disease (CKD). In certain circumstances, it is used as an alternate in patients who are intolerant to angiotensin converting enzyme inhibitors (ACE-i) 1 It selectively blocks angiotensin 1 receptor and hence it prevents the action of angiotensin II, a potent vasoconstrictor1 In the limited number of case report, there is a rare event of Valsartan-related cutaneous side effects manifestation2,3,4. This case report highlighted the rare skin manifestation related to Valsartan prescribed to control hypertension.